2021
DOI: 10.3389/fcell.2021.753279
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin Modulates Neural Stem Cells Fate Determination: In vitro Study on Human Neural Stem Cells, and in vivo Study on LPS-Induced Depression Mice Model

Abstract: Luteolin is a natural flavone with neurotrophic effects observed on different neuronal cell lines. In the present study, we aimed to assess the effect of luteolin on hNSCs fate determination and the LPS-induced neuroinflammation in a mouse model of depression with astrocytogenesis defect. hNSCs were cultured in basal cell culture medium (control) or medium supplemented with luteolin or AICAR, a known inducer of astrogenesis. A whole-genome transcriptomic analysis showed that luteolin upregulated the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 87 publications
(129 reference statements)
0
17
0
Order By: Relevance
“…Luteolin, a naturally occurring flavonoid, has been identified as one of the potential bioactive compounds with a variety of pharmacological effects. Research showed that luteolin could not only reduce the levels of pro-inflammatory factors TNF-α, IL-6, corticosterone, IL-17 and IL-23 [ 34 ], but also modulate Notch, FOXO, TNF, P53, Hippo, dopaminergic synapses and neurotrophin pathways [ 19 ]. Moreover, luteolin effectively reduced reactive oxygen species and thus improved nitric oxide utilization in venous endothelial cells [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Luteolin, a naturally occurring flavonoid, has been identified as one of the potential bioactive compounds with a variety of pharmacological effects. Research showed that luteolin could not only reduce the levels of pro-inflammatory factors TNF-α, IL-6, corticosterone, IL-17 and IL-23 [ 34 ], but also modulate Notch, FOXO, TNF, P53, Hippo, dopaminergic synapses and neurotrophin pathways [ 19 ]. Moreover, luteolin effectively reduced reactive oxygen species and thus improved nitric oxide utilization in venous endothelial cells [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the principle of random allocation, 40 mice were divided into five groups (8 mice in each group): control group, CUMS group, CUMS + Luteolin (5 mg/kg) group, CUMS + Luteolin (10 mg/kg) and CUMS + escitalopram group. Mariem Achour et al [ 19 ] demonstrated that luteolin (10 mg/kg) reversed LPS-induced depression-like behaviors in mice. Luteolin (5 and 10 mg/kg) was used in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Luteolin is reported to down-regulate the secretion of IL-1β, TNF-α, and IL-6 ( 26 28 ), suppress p65 and p38 phosphorylation in lipopolysaccharide (LPS)-induced C6 cells ( 26 ), inhibit nucleus p65, ASC, NLRP3, and cleaved-Caspase-1 protein expression, and increase Nrf2 protein in oxyhemoglobin-induced primary cortical neurons and glia cells ( 27 , 28 ). In LPS, Aβ 1-42 and triple-transgenic-induced AD mice, luteolin ameliorates behavior impairment, inhibits overproduction of pro-inflammatory mediators ( 26 , 29 31 ), as well as restrains GFAP, p38 protein expression and the phosphorylation of JNK and p65 ( 26 , 31 ). In other studies, luteolin is reported to decrease the release of pro-inflammatory mediators ( 27 , 28 ), decrease TRAF6, TLR4, and p-p65 expression as well as TRAF6 ubiquitination in the brain of intracerebral hemorrhage (ICH)-induced rats ( 27 ), suppress NLRP3 proteins expression and increase the activity of Nrf2 in the brain of subarachnoid hemorrhage-induced rats ( 28 ).…”
Section: Effects Of Natural Flavonoids On Neuroinflammationmentioning
confidence: 99%
“…Luteolin showed the potential of astrocyte differentiation for the rst time, thus highlighting its possible therapeutic role in neuroin ammatory and neurodegenerative diseases. Although the antidepressant behavioral effect of luteolin is not statistically signi cant, luteolin therapy regulates many signal pathways involved in the pathophysiology of depression [37].…”
Section: Antidepressant Effect Of Luteolinmentioning
confidence: 99%